Vietnam at a Crossroads : Engaging in the Next Generation of Global Value Chains - Hollweg, Claire H.; Smith, Tanya; Taglioni, Daria (Washington, DC: World Bank, 2017)
Vietnam is at a crossroads. It can grow as an export platform for GVCs, specializing in low value-added assembly functions with industrialization occurring in enclaves with little connection to the broader economy or society; or it can leverage the current wave of growth, enabled and accelerated by its successful participation in GVCs, to diversify and move up the chain into higher value-added functions. Success will require Vietnam’s policymakers to view the processes of development differently, and to take new realities of the global economy more fully into account.